Tuesday

July 22, 2014

July 22, 2014

Posted by **Anonymous** on Monday, December 9, 2013 at 12:58pm.

- MATH -
**SAM**, Monday, December 9, 2013 at 1:04pm2X-3Y=5

-2X -2X

-3Y=5-2X

DIVIDE BOTH SIDES BY -3

Y=-5/3+2/3X

NOW DO THE SAME FOR THE OTHER ONE PLUG THE -2 IN FOR X

Y=-5/3+2/3(-2)

PUT IN CALC WATCH SIGNS!!

Y=-3

- MATH -
**X**, Monday, December 9, 2013 at 2:53pmAll you have to do in this situation is substitute (-2) for the variable (x) in the equation. You can do this because all coordinates are of the form (x,y). Anything in the place of (x) can be seen as equal to (x). So, substituting, we can see:

2(-2) - 3y = 5

-4 - 3y = 5

-3y = 9

y = -3

As shown above, we can see that y = -3 when x = -2.

**Related Questions**

math - how do I solve this problem 2x/2=(6-3y)/2? 2x/2=(6-3y)/2? I solved it for...

math - A linear system may have a unique solution, no solution, or infinitely ...

math - hi, i need help with solving this equation for "y" 2x+3y=-2 2x+3y=-2 Get ...

correction of math - rewrite the equation 2x-3y= -6 as a function of x. My ...

math - 2x+3y=6 (solve for x) 2x+3y=6 Get unknown on one side and everything else...

Math - 2x-3y=6 I did +3y 2x=6+3y 1/2 to both sides(2x=3y/2+6) x=3/2y+6 or does ...

Math - Explain how to solve? Which equation below shows the equation y = – 1/4x...

math - A linear system may have a unique solution, no solution, or infinitely ...

Derive - Find the derivative of sin(2x + 3y)= 3xy + 5y-2. I have this so far 1) ...

Math - Solve the system using any algebraic method. 2x - 2y + z = 3 5y - z = -31...